Financial Management Practices Driving Sustainable Community Empowerment in Somongari Tourism Village - Ahmad Sofwan; Hari Purwanto; Lidya Fitri Yani; Dyah Palupiningtyas (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
This study examines the strategic role of financial management in empowering the community of Somongari Tourism Village, Purworejo Regency, which serves as a model of Community-Based Tourism (CBT). Despite its rich natural and cultural assets, the village faces challenges in sustaining tourism growth due to fluctuating visitor numbers, limited services differentiation, and uneven income distribution. The research aims to evaluate how transparent and participatory financial practices can strengthen community capacity, enhance homestay development, and ensure long-term sustainability. Employing a qualitative case study approach, data were collected through in-depth interviews with tourism managers and homestay operators, direct observation of community practices, and analysis of financial records and visitor data from 2023 to 2025. Findings reveal that inclusive organizational structures, collective price agreements, and youth-led digitalization initiatives foster social cohesion, accountability, and innovation, while service homogeneity and seasonal visitor fluctuations remain critical constraints. The synthesis highlights financial management not merely as a technical tool but as a catalyst for empowerment, enabling equitable income distribution, entrepreneurial growth, and resilience against market volatility. The study concludes that professional financial recording systems, continuous capacity-building, and collaboration among communities, government, and private stakeholders are essential to advance sustainable tourism development. Ultimately, financial management emerges as both a governance mechanism and a strategic pathway for balancing economic growth, cultural preservation, and community empowerment in Somongari Tourism Village.